Main Altar and Graves of the Padres, Mission San Carlos - John H. Atkinson, Jr.::::::photographer::: (Bell Magazine Agency)
Caption on back of card reads: 'Fray Junipero Serra, the apostle of California, is buried in the center tomb and beside him rest Padre Crespi, Lasuen and Lopez.'